Women, Sport and Baby-is it possible to do/have all? - Robert Kuchar (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2017)
Many women stand in their lives before one question-of family or child? When is the best time to have it, and what I want to accomplish before and also after childbirth. The same applies to the world of sport. On the contrary, many times it happens that successful athletes decide to end the career at an early age because of prioritizing the family, or vice versa-they prioritize sport at the expense of their family. The aim is to show that it may not always be the choice of either-or, but that it may be possible to combine maternal duties with the sport provided certain principles are followed. The research consists of two parts. The first part focuses on the period of pregnancy, ongoing changes in it (physical, psychological, etc.) and exercises that can be included in this period. The second chapter focuses on the period after childbirth and also on sports possibilities for mother and child life. To find the right path between sport and family life is not an easy way, but not impossible. Although motherhood is a relatively long time when a woman has to leave the sport, so it is not impossible to return and gain others sporting achievements. This study is descriptive and the data are secondary and were collected from valid documents. This study aims to investigate the way for girls and women's how to do not stop with sport and also have a "normal" family.